SNSE@POROUS CARBON NANOFIBERS AS A FREE-STANDING ANODE FOR LOW-TEMPERATURE LITHIUM-ION BATTERIES - Rakhmetova, Aiym; Nurpeissova, Arailym; Kalimuldina, Gulnur; Bakenov, Zhumabay (National Laboratory Astana, 2022)
Tin selenide-based materials are considered to be promising high-capacity anode materials for Li-ion batteries (LIBs) owing to their non-toxicity, earth-abundance, and chemical stability. However, SnSe suffers from a large volume expansion, which leads to poor cycling performance. In addition, it lacks in-depth research on low-temperature electrochemical performance...
Keywords: Type of access: Embargo; lithium-ion batteries